But Did You Use HydroCoil? Perianeurysmal Edema and Hydrocephalus with Bare Platinum Coils - White, J.B.; Cloft, H.J.; Kallmes, D.F. (American Journal of Neuroradiology, 2008)
SUMMARY: Bioactive coils were developed to improve aneurysm packing and accelerate neointimal healing. Recent reports, however, have implicated these coils in the development of aseptic meningitis, perianeurysmal edema, and hydrocephalus. This report demonstrates that the same clinical phenomena can occur with the use of bare platinum coils.